2002
DOI: 10.1093/ajcn/75.2.263
|View full text |Cite
|
Sign up to set email alerts
|

Validation of energy intake measurements determined from observer-recorded food records and recall methods compared with the doubly labeled water method in overweight and obese individuals

Abstract: Background: Measurements of dietary intake in obese and overweight populations are often inaccurate because food intakes are underestimated. Objective: The purpose of this study was to evaluate the validity of the combined use of observer-recorded weighed-food records and 24-h snack recalls in estimating energy intakes in overweight and obese individuals. Design: Subjects were 32 healthy women and 22 healthy men with mean body mass indexes (in kg/m 2 ) of 29.5 and 30.3, respectively. Energy intake (EI) was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
2
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 35 publications
(38 reference statements)
1
45
2
1
Order By: Relevance
“…One possible explanation for the more accurate reporting in children is that an observer (parent, caregiver) does the reporting (4,23) . Also Hise et al (6) found that the combination of observer-recorded food records with snack recalls is a valid method for measuring EI in overweight and obese subjects. Livingstone et al (1) concluded that parents can be reliable reporters of their children's food intake in the home environment, but probably not of their children's out-of-home food intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for the more accurate reporting in children is that an observer (parent, caregiver) does the reporting (4,23) . Also Hise et al (6) found that the combination of observer-recorded food records with snack recalls is a valid method for measuring EI in overweight and obese subjects. Livingstone et al (1) concluded that parents can be reliable reporters of their children's food intake in the home environment, but probably not of their children's out-of-home food intake.…”
Section: Discussionmentioning
confidence: 99%
“…The doubly labelled water (DLW) method is considered to be the 'gold standard' for the determination of total energy expenditure in free-living subjects (4) and has been used as a reference method in a large number of studies to validate energy intake both in adults (e.g. references [5][6][7][8] and children (e.g. references 1, 9-12).…”
mentioning
confidence: 99%
“…We have previously shown that women underestimated energy intake 7% compared to men when plate waste was compared to doubly labeled water. 29 Although we found no increase in energy intake for women, some of the energy intake such as snacks were gathered from recall methodology and may have been underestimated.…”
mentioning
confidence: 53%
“…33 EI was measured in this study using a combination of ad libitum meals in a university cafeteria and 24 hour recall-a technique previously shown to be accurate for total EI compared to doubly labeled water. 34 Overall the evidence suggests that there is no or a partial compensation for the exercise-induced energy deficit in overweight and obese individuals. However, increases in EI in response to long-term exercise have been reported in lean participants.…”
Section: Exercise and Weight Loss: Individual Variabilitymentioning
confidence: 99%